Avaliação de habilidades matemáticas de alunos com Transtornos do Espectro do Autismo - Fonteles, Daniel Sá Roriz (2012)
Currently, there are studies which advocate higher mathematical abilities in individuals with Autism Spectrum Disorders (ASD), namely Asperger Syndrome/High Functioning Autism, sometimes even declaring that these individuals do have an above average performance when compared to neurotypicals. When Hans Asperger first described the syndrome that takes his name, he observed that some of his patients exhibited some difficulties concerning the ability to perform arithmetic operations. The present research aims to better understand mathematic abilities of people with ASD, mainly because this area is still open and yet little explored, especially in Brazil. In order to do that, mathematical abilities of 20 ASD students, aging from 7 to 23 years, were investigated using an Arithmetic Test validated for children from 1st to 4th grade of the Brazilian school system (SEABRA et al., 2009). An exploratory study of qualitative and quantitative nature was performed, with detailed written record of each Arithmetic Test session, and the use of non-parametric statistics to verify possible interactions between variables. Comparison between Autism, Asperger and Normal Students groups were made, besides other variables taken from students files considered during this research. Results suggest that ASD students had similar performance to 1st graders of a public school in the State of São Paulo; and that ASD students who have had inclusive experiences in regular schools tend to get higher scores in the Arithmetic Test. Other considerations indicate that further research is needed to accomplish better ways to Mathematics teaching.